2018
DOI: 10.1007/s12035-018-1224-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Cognitive Impairment Is Associated with Cytokine Dysregulation and Disruptions in Neuroplasticity

Abstract: Chemotherapy-induced cognitive impairment, often referred to as "chemobrain," is a common side effect. In this study, mice received three intraperitoneal injections of a combination of docetaxel, adriamycin, and cyclophosphamide (DAC) at 2-day intervals. A water maze test was used to examine cognitive performance, and manganese-enhanced magnetic resonance imaging (MEMRI) was used to examine hippocampal neuronal activity. The whole brain, prefrontal cortex, hippocampus, and blood samples were then collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 42 publications
2
30
0
1
Order By: Relevance
“…A combination of oxygen radical production and cytokine dysregulation are the main suspects for chemobrain induction [2729]. It has been shown that aggressive, three- drug chemotherapy consisting of a combination of docetaxel, adriamycin, and cyclophosphamide led to a cytokine dysregulation and disruptions in neuroplasticity [30]. The mice subjected to chemotherapy in this study have spent less time in the target quadrant of the water maze in comparison to control mice.…”
Section: Chemobrainmentioning
confidence: 85%
“…A combination of oxygen radical production and cytokine dysregulation are the main suspects for chemobrain induction [2729]. It has been shown that aggressive, three- drug chemotherapy consisting of a combination of docetaxel, adriamycin, and cyclophosphamide led to a cytokine dysregulation and disruptions in neuroplasticity [30]. The mice subjected to chemotherapy in this study have spent less time in the target quadrant of the water maze in comparison to control mice.…”
Section: Chemobrainmentioning
confidence: 85%
“…The study found that the volume of hippocampus in the breast cancer group receiving chemotherapy was relatively low and was associated with higher TNF- α levels and lower IL-6 levels, providing a basis for inflammatory cytokine-mediated CRCI [ 25 ]. In addition to hippocampal dysfunction, increased cytokines caused by chemotherapy appear to be associated with disruption of neuroplasticity [ 26 ]. Cheung et al conducted a multicenter, prospective cohort study to verify the relationship between inflammatory cytokine levels and CRCI in breast cancer patients.…”
Section: Pathogenesismentioning
confidence: 99%
“…Few studies using animal models have examined the direct release of cytokines by activated microglia and astrocytes in the CNS. 5‐Fluorouracil and a combination of docetaxel, doxorubicin, and cyclophosphamide upregulated cytokines in the hippocampus (Groves et al , ; Shi et al , ). Methotrexate activated microglia, but no changes in CNS cytokine levels were observed (Seigers et al , ).…”
Section: Introductionmentioning
confidence: 99%